Pengenalan Metode Alat Kontrasepsi Guna Meningkatkan Keikutsertaan Dalam Menjadi Peserta Keluarga Berencana - Fika Aulia Aulia; Dwi Karika Sari Sari; Siti Maria Ulfa; Pratiwi Puji Lestari (CV. Multi Kreasi Media, 2022)
The intensive family planning program in most countries has had a significant effect. Indonesia has launched various programs to deal with population problems, is called National Family Planning Program. This program targets are divided into two, namely direct targets and indirect targets. There are many considerations that influence decision making in participating in the family planning program, so efforts are needed to assist the introduction of contraceptive methods and devices. The method used in this education is interactive education with pre-test and post-test. The results obtained from this activity are the achievement of maternal knowledge in the introduction of contraceptive methods and devices so that they decide to join the family planning program. The education provided interactively has a positive impact, so interaction in sharing information becomes more extensive and flexible. An increase in participants' knowledge of the importance of participating in family planning is indicated by the increased interest of participants in becoming a family planning participant. Interactive education for participants in this activity is effective in increasing the commitment of women of childbearing age who have not taken family planning to become family planning participants.